Bond strength of adhesive resin cement with different adhesive systems - e Silva, Fabrizio Lorenzoni; Pamato, Saulo; Kuga, Milton-Carlos; Só, Marcus-Vinicius-Reis; Pereira, Jefferson-Ricardo (Medicina Oral, S.L., 2017)
Background: To assess the immediate bond strength of a dual-cure adhesive resin cement to the hybridized dentin with different bonding systems. Material and Methods: Fifty-six healthy human molars were randomly divided into 7 groups (n=8). After 3 longitudinal sections, the central cuts were included in PVC matrix and were submitted to dentin hybridization according to the groups: G1 - etch & rinse system with 3-step (Apder™ Scotchbond™ Multi-Purpose, 3M ESPE), G2 - etch & rinse system with 3-step (Optibond™ FL, Kerr), G3 - etch & rinse system with 3-step (All-Bond 3®, Bisco), G4 - etch & rinse simplified system (Adper™ Single Bond 2, 3M ESPE), G5 - self-etching system with one step (Bond Force, Tokuyama), G6 - universal system in moist dentin (Single Bond Universal, 3M ESPE), G7 - universal system in dry dentin (Single Bond Universal, 3M ESPE). Then all groups received the cementing of a self-adhesive resin cement cylinder (Duo-link, Bisco) made from a polypropylene matrix. In the evaluation of bond strength, the samples were subjected to the microshear test and evaluated according to the fracture pattern by optical microscopy. Results: The Kruskal-Wallis test suggests a statistically significant difference between groups (p=0,039), and Tukey for multiple comparisons, indicating a statistically significant difference between G3 and G4 (p < 0.05). It was verified high prevalence of adhesive failures, followed by mixed failure and cohesive in dentin. Conclusions: The technique and the system used to dentin hybridization are able to affect the immediate bond strength of resin cement dual adhesive.
Keywords: Adhesion; Adhesive resin cement; Adhesive systems; Microshear